Peningkatan Kreativitas Anak Usia Dini Melalui Permainan Barongsai pada Peserta Didik Kelompok B TK Metta Maitreya Pekanbaru - Rida Jelita (STAB Maitreyawira, 2020)
Based on observations it was found that learning through the barongsai dance game can increase creativity in early childhood. This is proved by the increase in the percentage of creativity from before the action up to the second it proved by the increasing of creativity percentage before the teaching learning process until reach the cycle II, cycle I reached 51,02% or 25 children and the increaty of creativity on cycle II reached 81, 63 % or 40 children. This is because the barongsai dance stimulates children to think creatively, children have good attention to the learning process, children are able to organize their abilities or practice self-confidence in stimulate their imagination, improve their physical skill and gross motor skills so it can produce original games.